2022
DOI: 10.1038/s41598-022-11481-5
|View full text |Cite
|
Sign up to set email alerts
|

Indeterminacy of cannabis impairment and ∆9-tetrahydrocannabinol (∆9-THC) levels in blood and breath

Abstract: Previous investigators have found no clear relationship between specific blood concentrations of ∆9-tetrahydrocannabinol (∆9-THC) and impairment, and thus no scientific justification for use of legal “per se” ∆9-THC blood concentration limits. Analyzing blood from 30 subjects showed ∆9-THC concentrations that exceeded 5 ng/mL in 16 of the 30 subjects following a 12-h period of abstinence in the absence of any impairment. In blood and exhaled breath samples collected from a group of 34 subjects at baseline prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…The available literature does, however, suggest that ∆ 8 -THC and ∆ 9 -THC are pharmacodynamically quite similar (Hazekamp et al 2010 ; Abrahamov et al 1995 ; Kruger and Kruger 2021 ; Kruger and Kruger 2022 ), which is consistent with the findings of the present study. Prior to smoking ∆ 9 -THC in the previous study, the subjects showed no evidence of impairment despite measurable blood ∆ 9 -THC levels, which is consistent with recently published studies showing no significant correlation between impairment and specific blood concentrations of ∆ 9 -THC (Brubacher et al 2019 ; Hartman et al 2016 ; McCartney et al 2022 ; Hubbard et al 2021 ; Wurz and DeGregorio 2022 ).…”
Section: Discussionsupporting
confidence: 89%
“…The available literature does, however, suggest that ∆ 8 -THC and ∆ 9 -THC are pharmacodynamically quite similar (Hazekamp et al 2010 ; Abrahamov et al 1995 ; Kruger and Kruger 2021 ; Kruger and Kruger 2022 ), which is consistent with the findings of the present study. Prior to smoking ∆ 9 -THC in the previous study, the subjects showed no evidence of impairment despite measurable blood ∆ 9 -THC levels, which is consistent with recently published studies showing no significant correlation between impairment and specific blood concentrations of ∆ 9 -THC (Brubacher et al 2019 ; Hartman et al 2016 ; McCartney et al 2022 ; Hubbard et al 2021 ; Wurz and DeGregorio 2022 ).…”
Section: Discussionsupporting
confidence: 89%
“…The degree of impairment resulting from cannabis use is clearly related to the dosage administered (e.g., Schlienz et al, 2020). However, that relationship does not seem to translate into demonstrable dose-response relationship between the concentration of THC in the blood or oral fluid and either the level of impairment (Arkell et al, 2021; White and Burns, 2022b: 16-18; Wurz and DeGregorio, 2022) or the risk of crashing (Macdonald, 2018: 96; White and Burns, 2021: 12-13). Nevertheless, it is certainly possible to get so intoxicated on cannabis that one is incapable of safely driving a car.…”
Section: Discussionmentioning
confidence: 99%
“…The determination of therapeutic drugs in human breath has been reported 25 as well as toxicology applications where a number of abused drugs have been detected shortly after intake 26 . Part of the success of these easier sample collection techniques is the improvement in sensitivity and selectivity of modern LC/MS techniques 25,27–29 …”
Section: Introductionmentioning
confidence: 99%
“…26 Part of the success of these easier sample collection techniques is the improvement in sensitivity and selectivity of modern LC/MS techniques. 25,[27][28][29] In the recent past, a first-generation breath collection device was reported, which described the LC/MS/MS determination of a series of common drugs of abuse in subjects who had taken these drugs. 30 A subsequent report described the direct real-time measurement of volatiles in human breath with a compact mass spectrometer using atmospheric pressure chemical ionization (APCI) but without LC/MS coupling.…”
mentioning
confidence: 99%